Enhancing Interfaith Tolerance in PAI Learning: The Role of Interactive Digital Image Media in Multicultural Elementary Schools - Purnomo, Mohamad Edi; Muchtar, Asmaji; Makhshun, Toha (PPSDP International Journal of Education, 2025)
This study examines the implementation of interactive digital image media to enhance interfaith tolerance in Islamic Religious Education (PAI) at multicultural elementary schools. Using a qualitative approach, data were collected through interviews, observations, and document analysis from 15 fifth-grade students and one PAI teacher at SD Negeri Pulau Tembang. Findings revealed significant improvements in students’ understanding of tolerance and their attitudes toward religious diversity after eight sessions using interactive visuals (e.g., infographics, quizzes). The media fostered engagement, inclusive behavior, and reflective discussions. The study underscores the effectiveness of interactive digital tools in promoting tolerance and suggests their integration into PAI curricula. Limitations include the single-site design, warranting further research with broader samples.